2018
DOI: 10.1016/j.ncrna.2018.05.003
|View full text |Cite|
|
Sign up to set email alerts
|

BC200 (BCYRN1) – The shortest, long, non-coding RNA associated with cancer

Abstract: With the discovery that the level of RNA synthesis in human cells far exceeds what is required to express protein-coding genes, there has been a concerted scientific effort to identify, catalogue and uncover the biological functions of the non-coding transcriptome. Long, non-coding RNAs (lncRNAs) are a diverse group of RNAs with equally wide-ranging biological roles in the cell. An increasing number of studies have reported alterations in the expression of lncRNAs in various cancers, although unravelling how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 159 publications
(294 reference statements)
1
31
0
Order By: Relevance
“…BC200 RNA is involved in promoting the tumorigenesis and development of cancer cells through various mechanisms ( Samson et al, 2018 ; Shin et al, 2018 ). Since BC200 RNA knockdown reduces cell motility, we examined the effects of the extra adenine nucleotides on this cellular property.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BC200 RNA is involved in promoting the tumorigenesis and development of cancer cells through various mechanisms ( Samson et al, 2018 ; Shin et al, 2018 ). Since BC200 RNA knockdown reduces cell motility, we examined the effects of the extra adenine nucleotides on this cellular property.…”
Section: Resultsmentioning
confidence: 99%
“…In cancer of non-neuronal origins, BC200 RNA expression is activated ( Chen et al, 1997 ), possibly by cancer-specific factors. Recent studies have shown that the abnormal expression of BC200 RNA is related to the development of cancer cells through various mechanisms ( Booy et al, 2017 ; Hu and Lu, 2015 ; Peng et al, 2018 ; Ren et al, 2018 ; Samson et al, 2018 ; Shin et al, 2018 ; Singh et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This gene is derived from a monomeric Alu element and the transcript has a poly A region similar to BC1 RNA, but the overall sequences are very different [31,36]. However, research over the past three decades has confirmed that BC1 and BC200 RNA are functional analogues that perform the same function in each neuron through key common motifs including the GA kink motif, the poly A region, and the C-loop motif ( Figure 2) [32,[37][38][39].…”
Section: Bc Rnas: Bc1 and Bc200 Rnamentioning
confidence: 99%
“…The dysregulation of miRNAs has been reported to virtually occur in all types of cancers, including MM. Recent studies have provided evidence that long non‐coding RNAs (lncRNAs) are also involved in tumor initiation, metastasis, and drug resistance . LncRNAs, with a length of over 200 nucleotides, have little or no capacity for protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have provided evidence that long non-coding RNAs (lncRNAs) are also involved in tumor initiation, metastasis, and drug resistance. 6 LncRNAs, with a length of over 200 nucleotides, have little or no capacity for protein synthesis. These have been shown to regulate gene expression at the transcriptional, post-transcriptional, and epigenetic levels 7 and are implicated in diverse biological functions, including development, proliferation, differentiation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%